Bacteriophage Therapy Testing Against Shigella flexneri in a Novel Human Intestinal Organoid-Derived Infection Model. Issue 4 (April 2019) - Llanos-Chea, Alejandro; Citorik, Robert J.; Nickerson, Kourtney P.; Ingano, Laura; Serena, Gloria; Senger, Stefania; Lu, Timothy K.; Fasano, Alessio; Faherty, Christina S.
ABSTRACT: Objective: Enteric bacterial pathogens cause diarrheal disease and mortality at significant rates throughout the world, particularly in children younger than 5 years. Our ability to combat bacterial pathogens has been hindered by antibiotic resistance, a lack of effective vaccines, and accurate models of infection. With the renewed interest in bacteriophage therapy, we sought to use a novel human intestinal model to investigate the efficacy of a newly isolated bacteriophage against Shigella flexneri . Methods: An S. flexneri 2457T-specific bacteriophage was isolated and assessed through kill curve experiments and infection assays with colorectal adenocarcinoma HT-29 cells and a novel human intestinal organoid-derived epithelial monolayer model. In our treatment protocol, organoids were generated from intestinal crypt stem cells, expanded in culture, and seeded onto transwells to establish 2-dimensional monolayers that differentiate into intestinal cells. Results: The isolated bacteriophage efficiently killed S. flexneri 2457T, other S. flexneri strains, and a strain of 2457T harboring an antibiotic resistance cassette. Analyses with laboratory and commensal Escherichia coli strains demonstrated that the bacteriophage was specific to S. flexneri, as observed under co-culture conditions. Importantly, the bacteriophage prevented both S. flexneri 2457T epithelial cell adherence and invasion in both infection models. Conclusions: Bacteriophages offer feasible alternatives to antibiotics for eliminating enteric pathogens, confirmed here by the bacteriophage-targeted killing of S. flexneri . Furthermore, application of the organoid model has provided important insight into Shigella pathogenesis and bacteriophage-dependent intervention strategies. The screening platform described herein provides proof-of-concept analysis for the development of novel bacteriophage therapies to target antibiotic-resistant pathogens. Abstract : Supplemental Digital Content is available in the text